Development of a Muslim student happiness model through student engagement, friendship quality and positive thinking: Moderators of religious orientation in Southeast Asia - Fitriah M. Suud; Mirawati Mirawati; Putri Rahmah Nur Hakim; Muhammad Fadli Nugraha; Tri Na'imah; Kartini R. Tahir (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2026)
Promoting student happiness has become a growing priority in educational psychology because of its role in adolescent well-being. This study aims to test a comprehensive model of student happiness by analyzing the role of student involvement, friendship quality and positive thinking, with religious orientation as the moderating variable. A non-experimental quantitative design was used involving 1,217 Muslim junior high school students from Indonesia, Malaysia and the Philippines. Data were collected using validated instruments and analyzed using partial least squares–structural equation modeling (PLS-SEM) with SmartPLS 3.0. The results show that student engagement (β = .254; t = 9.499; p < .001), friendship quality (β = .221; t = 7.136; p < .001), and positive thinking (β = .191; t = 6.738; p < .001) significantly predicted student happiness. Religious orientation significantly moderated the relationships between positive thinking and happiness (β = .094; t = 2.981; p = .002) and between student engagement and happiness (β = .104; t = 3.059; p = .001), but not friendship quality (β = .020; p = .293). The model explained 38.7% of the variance in student happiness. The findings provide an alternative explanation for student happiness by integrating psychosocial and spiritual factors in Southeast Asian cross-cultural contexts. The results also offer practical implications for educators and policymakers in the design of holistic interventions that increase student engagement, foster quality friendships, promote positive thinking, and integrate religious values to support student well-being.